Study the Prophylactic Role of Anti-Type IV Pili (fimbriae) Antibody Against Pulmonary Infection Caused by P.aeruginosa in vivo (mice) - A. Abu Resha, Rasmia; B. Al-Zubaidy, Basma (Iraqi Journal of Science, 2023)
This study was aimed to investigate the effect of anti- type 4 pili antibody inprevention pulmonary infections caused by P. aeruginosa in vivo. This wasachieved by Evaluation of biofilm formation by the microtiter plate method toselect P.aeruginosa isolate with highest biofilm formation capacity, Extractionand the partial purification of type IV pili from the selected isolate, thenPreparation of type IV pili antibodies by rabbit immunization. The lunghistological sections of non immunized mice were severly damaged ,while thedamage were markedly decrease in the lung of immunized mice with anti-type 4pili antibody.